KONSEP ITTISHAL AL-SANAD SEBAGAI SYARAT KAJIAN KITAB KUNING DALAM TRADISI PESANTREN AN-NAHDLIYYAH CIREBON - Anisatun Muthi`ah; Luqman Zain MS (IAIN Syekh Nurjati Cirebon, 2020)
The process of transferring knowledge from teacher to student is also called the transmission of knowledge in the boarding school environment carried out by maintaining the tradition of continuation of sanad, sanad diploma. this allows the teachings delivered at the pesantren to the authors of the book to be continued to the Prophet. At this time of the millennial era there are some people who study religion without going through a clear teacher. Some have learned from social media, Facebook and YouTube networks, because in this technological era anyone can easily access it, both across regions and times. But the tradition at An-Nahdliyyah Islamic Boarding School in Cirebon still maintains a continuation tradition. This article explains the concept of ittishal sanad in scientific transfer. This study uses a qualitative approach with data collection techniques through observation and interviews. The results show that the concept of ittishal al-sanad in Pondok Pesantren an-Nahdliyyah Gebang is a clear connection (mu’tamad) in the scientific transmission between teacher and student. it’s clear where he got it from. The continuation of the sanad is similar to the chain of the narrators of the narrators of the hadith, but the series of the narrators ends in the last rawi as book mushannif because the hadith has been recorded (tadwin), whereas in scientific transmission especially in the pesantren boarding school the continuation of the teachers and students will continue, until the end of the period . And for original and caution, it is expected that all types of knowledge must know the continuity of their sanad. Keywords: Ittishal Al-Sanad, Tradition, An-Nahdliyyah Islamic Boarding School